Socio-demographic and Clinical Factors Associated with the Deliveries of Babies ‘Born Before Arrival’ at Swartruggens Hospital between 2013 and 2014 - Oluwole, Oladotun Koledola (My University, 2018)
Background: It has been established that morbidity and mortality documented in babies ‘born before arrival’ (BBBAs) and their mothers are worse when compared to those of hospital deliveries. Pregnant women who deliver their newborns at home before bringing them to Swartruggens Hospital expose themselves and their newborns to these worse clinical outcomes. Aim: To determine the socio-demographic and clinical factors associated with the delivery of babies ‘born before arrival’ at Swartruggens Hospital between 2013 and 2014 Methods: The research was an unmatched case-control study in which mothers who delivered BBBAs were the cases and mothers who delivered in the hospital were the controls. A two-year retrospective review was conducted on the medical records of the two groups of mothers and their respective babies at Swartruggens Hospital between 2013 and 2014. Data were obtained on sociodemographic variables such as age, marital status, race, education status, estimated distance from home to hospital and clinical variables like parity, booking status, booking trimester, sufficiency of ANC visits, time of delivery. STATA 14 was used to analyse the data. Results: The following sociodemographic and clinical factors were associated with the home delivery of BBBAs: primary education or none (aOR=2.98, 95% CI=1.42 6.27,p=0.0040), insufficient ANC visits (aOR=3.86, 95% CI=1.62-9.21,p=0.0020), preterm gestational age at delivery (aOR=2.43, 95% CI=1.14-5.21,p=0.0210) and delivery of baby at night time (aOR=9.05, 95% CI=4.15-19.67,p=0.0000). Complications such as low birthweight, prematurity, hypothermia, hypoglycaemia, neonatal sepsis and neonatal jaundice were more prevalent in the BBBAs. Conclusion: The findings in this study suggest that the following interventions may reduce the incidence of BBBAs. These interventions include: promulgating governmental policies that ensure that the girl child achieves secondary education at the minimum; the promotion of community awareness and health education for pregnant women that emphasizes the importance of early booking for antenatal care (ANC), attending minimum 4 ANC visits and the delivery of newborns inside hospital. The designation of ambulances solely for the maternity wards of rural hospitals to bring in pregnant women in labour to the hospital at any time could be another intervention.
A research report submitted to the Faculty of Health Sciences, University of Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Public Health (MPH), 2018